2020
DOI: 10.1111/mcn.12957
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable mothers' experiences breastfeeding with an enhanced community lactation support program

Abstract: The Canada Prenatal Nutrition Program (CPNP) provides a variety of health and nutrition supports to vulnerable mothers and strongly promotes breastfeeding but does not have a formal framework for postnatal lactation support. Breastfeeding duration and exclusivity rates in Canada fall well below global recommendations, particularly among socially and economically vulnerable women. We aimed to explore CPNP participant experiences with breastfeeding and with a novel community lactation support program in Toronto,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 40 publications
0
79
1
1
Order By: Relevance
“…Skilled lactation support in the first two weeks postpartum is known to be critical for the management of breastfeeding difficulties [21,45]. Our qualitative work investigating mothers' experiences with the 5Ps CPNP lactation support program found that the lactation services were highly valued and helped address physical, practical and self-efficacy challenges related to breastfeeding [27]. These findings are encouraging given the 5Ps CPNP's mandate for reducing inequities in service provision for vulnerable women in the perinatal period.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Skilled lactation support in the first two weeks postpartum is known to be critical for the management of breastfeeding difficulties [21,45]. Our qualitative work investigating mothers' experiences with the 5Ps CPNP lactation support program found that the lactation services were highly valued and helped address physical, practical and self-efficacy challenges related to breastfeeding [27]. These findings are encouraging given the 5Ps CPNP's mandate for reducing inequities in service provision for vulnerable women in the perinatal period.…”
Section: Discussionmentioning
confidence: 69%
“…Canadian guidelines acknowledge the importance of skilled lactation support in the community for new mothers and suggest direct assessment and follow up by skilled lactation professionals [9,37], but private IBCLCs are not covered by provincial health insurance in Ontario and thus are typically only accessible to higherincome women. Free community breastfeeding services are typically offered reactively and are harder to access by vulnerable women [27]. Together, the data from our current study and our qualitative work suggest that a demand exists for skilled breastfeeding support among vulnerable women and that such services can be delivered through a CPNP site.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations